Rancang Bangun Web Pengelolaan Hutan Rakyat Dengan Metode Personal Extreme Programming - Dipa Maulana Rifqi Wicaksana; Evi Dwi Wahyuni; Ilyas Nuryasin (Jurnal Repositor, 2023)
In the last few years software has developed very rapidly around the world. Various methods are used to build the project according to the needs of client. Not all clients can clearly describe their needs and tend to change following the software development process. This development cannot be done if the software development method is still conventional. One of the software development methods that can follow changes from the client is Extreme Programming. Being flexible and able to provide results according to client requirements, Extreme Programming is the right choice for software development that requires relatively short development time and only one developer member makes this method suitable for use in small projects with short durations. Combined with the MoSCoW method to determine priority values, it will be easier for developers to determine the best needs for clients.